Traumatic stigmatisation and rejection of migrant mine labourers due to HIV and AIDS in the Welkom area : a pastoral care perspective - Masango, Maake J.S (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2011.